Bewitched, bothered, and biscotti - Cates, Bailey (New York : Obsidian, 2012)
As a new witch and owner of Savannah's most enchanting bakery, Katie Lightfoot is still getting used to casting spells, brewing potions, and mastering her magical powers. Then she stumbles upon a corpse during a picnic with firefighter Declan McCarthy. The dead man's tattoo reveals he was a member of a secret society, and it turns out he's missing an object that was very important to the group. When Katie learns the killer was after more than the man's life, she and her Aunt Lucy leave the baked goods on the rack to cool and set off in hot pursuit of a killer.
"An Obsidian mystery."
Keywords: Bakers -- Fiction; Bakeries -- Fiction; Magic -- Fiction; Blessing and cursing -- Fiction; Murder -- Investigation -- Fiction; Witches -- Fiction; Aunts -- Fiction; Baking -- Fiction; Savannah (Ga.) -- Fiction; Georgia -- Fiction; Detective and mystery fiction; Paranormal fiction